AuS and SH bond formation/breaking during the formation of alkanethiol SAMs on Au(111): A theoretical study - Tielens, Frederik (2010)
The bonding of propanethiol molecules on a Au(111) surface is investigated using period DFT calculations within the framework of our model for chemical bond breaking that was recently proposed. The S-H bond breaking and the Au-S bond formation are analyzed through the evolution of the density of states. The energetics confirms the complexity of the reaction emerging from the interthiol chain interaction. The formation of a self-assembled monolayer is explained through a two-step mechanism, S-H bond breaking and Au-S bond formation. The production of H2 is found to be more favorable than the formation of Au-H species. The bonding and antibonding electronic states of the S-H bond have been identified and their evolutions during the process of bond breaking carefully analyzed. The corresponding bonding and antibonding states for the C-S bond are practically not affected during this process, indicating that the bond is preserved. The s orbital of the hydrogen atom strongly interacts with the gold surface and finally a Au-H bond is formed.